2017
DOI: 10.1002/bem.22086
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Arabidopsis flowering by near‐null magnetic field is mediated by auxin

Abstract: We previously found that flowering of Arabidopsis was suppressed by near-null magnetic field, which was related to cryptochrome. Auxin plays an important role in Arabidopsis flowering. To test whether auxin is involved in the suppression of Arabidopsis flowering by near-null magnetic field, we detected auxin level and expressions of auxin transport and signaling genes in wild-type Arabidopsis plants and cryptochrome double mutant, cry1/cry2, grown in near-null magnetic field. We found that indole-3-acetic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
(52 reference statements)
5
37
0
Order By: Relevance
“…We previously found that flowering of Arabidopsis in near-null magnetic field was delayed, which was blue light dependent, suggesting that cryptochrome is involved in the effect of near-null magnetic field on Arabidopsis flowering [Xu et al, 2012[Xu et al, , 2015. We also found that phosphorylation and dephosphorylation of cryptochrome were affected by near-null magnetic field, implying that function of cryptochrome can be modified by near-null magnetic field [Xu et al, 2014].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We previously found that flowering of Arabidopsis in near-null magnetic field was delayed, which was blue light dependent, suggesting that cryptochrome is involved in the effect of near-null magnetic field on Arabidopsis flowering [Xu et al, 2012[Xu et al, , 2015. We also found that phosphorylation and dephosphorylation of cryptochrome were affected by near-null magnetic field, implying that function of cryptochrome can be modified by near-null magnetic field [Xu et al, 2014].…”
Section: Discussionmentioning
confidence: 76%
“…Cryptochrome plays a major role in photoperiodic flowering of Arabidopsis [Guo et al, ; Mockler et al, , ; Lin, ]. We previously found that flowering of Arabidopsis was suppressed by near‐null magnetic field, which was mediated by functional modification of cryptochrome [Xu et al, , , , ]. We then wanted to disclose the physiological mechanism of the effect of near‐null magnetic field on Arabidopsis flowering, and the relation between physiological changes and cryptochrome in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the radical pair theory, an external magnetic field affects chemical reactions by alternating electron spin state of a weakly coupled radical pair, which is produced as an intermediate of the electron transport chain reactions [Zhang et al, ]. This has been proved in plant, drosophila and migrating birds [Gegear et al, ; Zhang et al, ; Xu et al, ]. Foley et al [] showed that human cryptochrome could restore the magnetosensation of cry‐knock out Drosophils, which suggest that mammalian also share a similar radical pair reaction‐based magnetosensation.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, recent reports revealed that variation of MF intensity affects photoreceptor activity (Agliassa et al, 2018b) and light-dependent processes such as leaf movement, stomatal conductance, and chlorophyll content (Galland and Pazur, 2005;Maffei, 2014). Furthermore, changes in the hormone levels, for instance, auxin and gibberellin, as well as a delay in flowering time have also been observed under near null MF (NNMF) conditions (Xu et al, 2012(Xu et al, , 2017(Xu et al, , 2018Agliassa et al, 2018a). Such delayed transition to flowering under NNMF is likely involved in the Angiosperms speciation during GMF reversals (Maffei, 2014;Occhipinti et al, 2014;Bertea et al, 2015), suggesting a possible contribution of the GMF magnitude on plant evolution.…”
Section: Introductionmentioning
confidence: 99%